Perceptions, Motivations, and Concerns about Living Organ Donation among People Living with HIV - Van Pilsum Rasmussen, Sarah E. (AIDS Care, 2018)
Recent changes to United States law now permit people living with HIV (PLWH) to donate organs to HIV-infected (HIV+) recipients under research protocols. PLWH may have unique motivations for and concerns about living donation and understanding them is critical to ensuring the integrity of this novel approach to organ transplantation. We interviewed PLWH from an urban HIV clinic who had previously indicated their willingness to be a living donor. In-depth interviews elicited information about their motivations, perceived benefits, and concerns about living donation. Codes were identified inductively and then organized into themes and subthemes. Two coders analysed independently the interviews and reconciled differences in coding by consensus. Thematic saturation was reached after 20 interviews. Motivations for living donation among PLWH included an altruistic desire to help others as well as HIV-specific motivations including solidarity with potential recipients and a desire to overcome HIV-related stigma. Perceived benefits of living donation included gratification from saving or improving the recipient’s life and conferring a sense of normalcy for the HIV+ donor. Concerns about donation included the possibility of a prolonged recovery period, organ failure, and transmission of another strain of the virus to the recipients. PLWH had unique motivations, perceived benefits, and concerns about living donation in addition to those previously identified in the general population. These unique factors should be addressed in research protocols, informed consent processes, and the education and training of independent living donor advocates so that these endeavors are ethically sound.